Environmental taxes and specialties in the taxation of the province of Galápagos - Pérez Zúñiga, José María (Revista Universidad de Guayaquil, 2015)
The environmental taxes, green taxes or ecotaxes, have their reason for being, in the protection of the environment and in the extra fiscal purposes, that in Ecuador acquire special relevancy. It would be advisable that the entry tax for tourists in Galapagos, adopts the form of an administrative rate for accomplishment of tourist activities in a specially protected areas.